Assessment of Students' Talent and Interest In Arabic Subjects Through A Behavioral Approach At MI Ma'arif Kliwonan - Krisdayanti, Aprilia Rotul; Azmi , Fery Maulana; Khoerunnisa, Sitta Latifah; Wildasari , Sania; Zakly, Abiyyu; Elfath, Silma Dianaty; Fatkhurrohman, Fatkhurrohman (DAS Institute, 2023)
The objective of this research is to determine students' interests and talents in learning Arabic by applying it through a behaviorist approach at MI M'a'arif Kliwonan. The target of this interest and talent assessment research is students and teachers in Arabic language subjects. The data collection technique in this research is interviews, the results of this research show that students lack interest and talent in Arabic language subjects. Through this research, it is hoped that schools can improve the quality of students' interests and talents.